Convergent Synthesis of Novel Mono- and Di-substituted 1,2-Isopropylideneglucofuranose Appended Dendrimers with a Ferrocene Core and their Electrochemical Studies - Ray, Ankur; Khan, Sabiha (Synlett, 2018)
Ferrocene-cored dendrimers incorporating 1,2-isopropylidenefuranose capped furanoside branches were synthesized and their electrochemical properties were studied. It was observed that the dendritic environment in the ferrocene dendrimers increased the E1/2 values with increase in bulk of the dendrimer, as expected. The reversible nature of the redox process was maintained in all the dendrimers.
Keywords: 1,2-isopropylidenefuranose; ferrocene; dendrimers; electrochemical properties